Cross-Border Transmissions of the Delta Substrain AY.29 During Tokyo Olympic and Paralympic Games - Koyama, Takahiko; Tokumasu, Reitaro; Katayama, Kotoe; Saito, Ayumu; Kudo, Michiharu; Imoto, Seiya (Frontiers in Microbiology, 2022)
Tokyo Olympic and Paralympic Games, postponed for COVID-19 pandemic, were finally held in summer of 2021. Just before the games, the Alpha variant was being replaced with the more contagious Delta variant. AY.4 substrain AY.29, which harbors two additional characteristic mutations of 5239C>T(NSP3 Y840Y) and 5514T>C(NSP3 V932A), emerged in Japan and became dominant in Tokyo by the time of the Olympic Games. Variants of SARS-CoV-2 genomes were performed to extract AY.29 Delta substrain samples with 5239C>T and 5514T>C. Phylogenetic analysis was performed to illustrate how AY.29 strains evolved and introduced into countries abroad. Simultaneously, ancestral searches were performed for the overseas AY.29 samples to identify their origins in Japan using the maximum variant approach. As of January 10, 2022, 122 samples were identified in 20 countries. Phylogenetic analysis and ancestral searches identified 55 distinct introductions into those countries. United States had 53 samples with 10 distinct introductions, and United Kingdom had 13 distinct strains introduced in 23 samples. Other countries or regions with multiple introductions were Canada, Germany, South Korea, Hong Kong, Indonesia, Thailand, and Philippines while Italy, France, Spain, Sweden, Belgium, Peru, Australia, New Zealand, Israel, Turkey, and Canary Islands had only a single strain. Most of those 20 countries have high vaccination rates and sufficient genomic surveillances; transmissions seem contained. However, propagations to unvaccinated regions might have caused unfathomable damages. Since samples in those unvaccinated countries are also undersampled with longer lead time for data sharing, it will take longer to grasp the whole picture. More rigorous departure screenings for the participants from the unvaccinated countries might have been necessary.